Jawabanmu

2014-05-05T19:16:17+07:00
F(x) = ax+b ---- f(-1) = 9               ---- f(2) = -3
9 = -a + b
-3 = 2a + b
------------------  -
12 = 3a
a = 4

-3 = 2(4) + b
-3 = 8 + b
- b = 8 + 3
 b = -11 

f(-3) = 4(-3) + -11
= -12 + -11
= -23

jadikan yang terbaik ya
f(x) = ax+b ---- f(-1) = 9 ---- f(2) = -3
9 = -a + b
-3 = 2a + b
------------------ -
12 = -3a
a = -4 f-1=-4.-1+b=9
=4+b=9
=b=5
jadi f(-3) adalah = -4*-3 =5 . 12+5 = 17
2014-05-05T19:20:33+07:00
(f-1=-1a+b=9) - (f2=2a+b=-3) = -3a=12 a=-4
f-1=-4.-1+b=9
    =4+b=9
    =b=5
f-3=-4.-3+5
    =12+5=17